Portrait of Online Learning during the Covid-19 Pandemic (a Case Study on Solo Raya Vocational Teacher) - Siswandari, Siswandari; Sumaryati, Sri; Susilaningsih, Susilaningsih; Susanti, Asri Diah; Hamidi, Nurhasan; Muchsini, Binti; Muhtar, Muhtar (Teknodika, 2021)
This study aims to identify the implementation of online learning conducted by teachers to provide the best service to students. This can be seen from health, fitness, spirit, duration of services related to education, applications used, signal conditions, teacher readiness in providing services outside the provisions of working hours, available learning facilities, and several other online learning activities Covid-19 pandemic. This study involved 254 vocational school teachers in Solo Raya. Quantitative data is netted through questionnaires that are disseminated using Google Form facilities. Meanwhile, we obtained qualitative information from interviews designed using WhatsApp and telephone facilities. The results showed that 52.2% of teachers admitted to agreeing not to have any health complaints. Teachers are always fit for online learning, with 58.9% agreeing. Teachers were always excited when they were online, with 68.4% answering agreed. The implementation of online learning requires more service time. 64.9% of teachers provide services about 14 hours per day. 64.1% of teachers agreed that they are ready to provide online services to students outside the working hours. Teachers have RPP as a sign of online learning, with 68.8% of teachers agreeing